Post exercise protein feeding does not alter molecular markers of translation initiation or measures of skeletal muscle function - Stob, Nicole R., author (Colorado State University. Libraries, 2004)
Resistance exercise stimulates skeletal muscle protein synthesis (SMPS) and breakdown; the pathway that predominates post-exercise appears to be influenced by nutrient intake before, during, and following exercise. Accordingly, insulin and amino acids have been shown to stimulate SMPS, appearing to activate proteins involved in translation initiation termed eukaryotic initiation factors (eIFs) (Jefferson & Kimball, 2003; Kimball, et al., 2002). An increase in translation initiation appears to be characterized by increased phosphorylation of eIF4E binding protein-1 (4EBP1) and decreased phosphorylation of eIF2α (Jefferson & Kimball, 2003). This study was undertaken to determine the effect of ingesting carbohydrate (CHO) or carbohydrate+protein (CP) on the phosphorylation of skeletal muscle 4EBP1 and eIF2α following eccentric exercise. CP ingestion was hypothesized to significantly increase the phosphorylation of 4EBP1 and decrease the phosphorylation of eIF2α in comparison to CHO. Thirty-six untrained adult males performed eccentric leg extensions at 130% of their concentric one-repetition maximum followed by consumption of water (CON), CHO, or CP. There was no significant time effect (4EBP1 p=.15, eIF2α p=.49) or treatment effect (4EBP1 p=.43, eIF2α p=.46) for phosphorylation of 4EBP1 or eIF2α, nor was there a significant time by treatment interaction (4EBP1 p=.44, eIF2α p=.69). Therefore, the ingestion of CHO or CP following intense eccentric exercise does not appear to alter the phosphorylation of 4EBP1 or eIF2α. Eccentric exercise typically induces delayed onset muscle soreness (DOMS) within 24 hours. Several methods of preventing and/or treating DOMS have been proposed; no single method has proven effective, however. In this area, nutrition has not been extensively studied. This study investigated the affect of post-exercise nutrition (CON, CHO, or CP) on muscle soreness, maximal leg extension, and vertical jump following eccentric exercise. It was hypothesized that the CP group would improve the time-course of recovery from eccentric exercise when compared with the CHO or CON groups. Despite significant time effects for skeletal muscle soreness, strength, and vertical jump (soreness and strength p<001, vertical jump p=.01), no differences were observed between the treatment groups for these variables. Therefore, post-exercise nutrition may not be effective in alleviating DOMS or promoting recovery of muscular performance.
Keywords: nutrition; molecular biology